Study on the influence of ultrasonic impact treatment (UIT) on stress evaluation of laser cladding coating by using metal magnetic memory technology. (January 2023) - Liu, Bin; Fu, Peng; Gu, Jiayang; He, Peng; Fang, Jinxiang; Dong, Lihong
Highlights: Magnetic field intensity gradient of H p ( y ) signal could be used to evaluate stress of laser cladding coating. Repetition rate of UIT effect on magnetic field intensity gradient of H p ( y ) signal was analyzed. By using MMMT and UIT, a method for controlling stress of laser cladding coating was proposed. Changes of microstructure and deformation of coating caused by UIT were main reasons for results. Abstract: The effect of ultrasonic impact treatment (UIT) on stress of laser cladding coating evaluated with metal magnetic memory technology (MMMT) was discussed, so a stress control method was proposed. In this paper, a metal magnetic memory testing device of EMS-2003, a two-channel pen metal magnetic memory probe and a non-ferromagnetic three-dimensional electronically controlled displacement plat form were employed to collect H p( y ) signal defined as the normal component of MMM signal, and tensile test was carried out on LC-50 testing machine. To prove the theoretical analysis, the microstructure and three dimensional surface topography of coating under different repetition rates of UIT were observed by using optical microscope and laser scanning confocal microscopy. The results show that the influence of detection line on H p( y ) signal can be ignored, and the distribution of H p( y ) signals under different tensile loads are all approximately an oblique line, which can be explained by the magnetic dipole model. As tensile load increases, the magnetic field intensity gradient of H p( y ) signal ( K ) becomes higher, and after coating is in the plastic deformation state, the value of K becomes lower gradually as tensile load increases further. When tensile loads are the same, the value of K becomes higher gradually as the repetition rate of UIT increases. But as repetition rate of UIT increases, the slope of K becomes lower gradually, and the changes on microstructure and deformation caused by UIT are seen as main reasons. At last, the experimental results were theoretically discussed based on the magnetostriction effect, and it was thought that the change on orientation of magnetic domain was the main reason.